Credible disinflation and delayed slumps under real wage rigidity - Mewael Tesfaselassie (Kiel Institute for the World Economy (IfW), 2014)
The paper studies the effects of credible disinflation in the presence of real wage rigidity, comparing the Calvo and Rotemberg price setting mechanisms (the two popular variants of the New-Keynesian model). In both types of models, a credible, gradual disinflation is shown to lead to a delayed slump in output along the transition path. The delayed-slump result is novel and owes to negative real wage growth along the transition path, whose effect is amplified by the degree of real wage rigidity.
Keywords: E31; E50; 330; sticky prices; real wage rigidity; disinflation; nonlinear dynamics